In Enemy Hands : A Prisoner in North Korea - Zellers, Larry (Book collections on Project MUSE., 2014)
"" A newly married Methodist minister, Larry Zellers was serving as a missionary and teacher in a small South Korean town near the 38th parallel when he was captured by the North Koreans on June 25, 1950. Until his release in 1953, Zellers endured brutal conditions and inhumane treatment. Through his story, Zellers shows that, despite the opinion that POWs live only for themselves, many in the camps worked to help others and conducted themselves with honor.